2018
DOI: 10.1037/per0000286
|View full text |Cite
|
Sign up to set email alerts
|

Initial development of pathological personality trait domain measures using the Personality Assessment Inventory (PAI).

Abstract: This study set out to create measures of the five personality disorder trait domains outlined in Section III of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (American Psychiatric Association, 2013) from the Personality Assessment Inventory items (Morey, 2007). Rasch rating scale model analyses and classical test theory analyses were applied to existing data sets (N = 3,877; community, clinical, offender, college) to identify relevant items. Five scales were created that had acceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Our findings add to the extant literature on analysing PAI items to predict a number of patient variables, such as malingering, pathological traits, behaviour change and suicide risk (Aita et al, 2017;Gaines et al, 2013;Penson et al, 2018;Ruiz et al, 2018;Sinclair et al, 2016). Additionally, our present findings expand on findings from our previous work (Cersosimo et al, 2021), which revealed that patients who reported lower early session alliance also reported more ANT; specifically, more antisocial behaviours and therapists reported higher early session alliance with patients who reported more ARD, specifically those with traumatic stress.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our findings add to the extant literature on analysing PAI items to predict a number of patient variables, such as malingering, pathological traits, behaviour change and suicide risk (Aita et al, 2017;Gaines et al, 2013;Penson et al, 2018;Ruiz et al, 2018;Sinclair et al, 2016). Additionally, our present findings expand on findings from our previous work (Cersosimo et al, 2021), which revealed that patients who reported lower early session alliance also reported more ANT; specifically, more antisocial behaviours and therapists reported higher early session alliance with patients who reported more ARD, specifically those with traumatic stress.…”
Section: Discussionsupporting
confidence: 80%
“…In a study by Ruiz et al (2018), researchers developed PAI measures of five pathological character trait domains from the Diagnostic Statistical Manual of Mental Disorders (DSM-5) reflected in the study by PID-5 (Personality Inventory for DSM-5; Krueger et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, disorderspecific impairment scales of criterion A have been developed that allow for investigating whether the individual impairment criteria for the six specific PDs listed under the rubric of criterion A are valid and useful [87, 88••, 89]. Moreover, it has been shown that the Personality Assessment Inventory (PAI) [90], a well-established broadband clinical self-report measure, can be scored to recover the DSM-5 trait domains and facets [91,92]. For the purpose of assessing dynamic changes in personality pathology, ambulatory assessment measures have been applied with the potential to uncover nuanced temporal dynamics of impairments and maladaptive trait expressions [45,49,93].…”
Section: Further Issuesmentioning
confidence: 99%